Pengaruh kerapatan tanaman dan frekuensi penyiangan terhadap pertumbuhan dan hasil jagung(Zea mays L.) varietas arjuna pada lahan kering= The effect of population density and weeding frequency to growth and yield of cor - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
ABSTRACT Plant spacing and population density requirement are different among corn cultivars and among soil types to get the maximum yield. The purpose of this experiment is to study the effect of plant spacing, population density and weeding frequency to growth and yield of corn, Arjuna variety on grumusol soil type. The experiment was 6 x 2 factorial arranged in randomized complete block with three replications. The first factor is population density that is plant spacing and plant number per hill combination, the second factor is weeding frequency. Population density influences the growth and yield. Up to 66.666 plants per hectare, the more plant density, the more yield. At the combination of 66.666 plants population and twice weeding produced the best yield. On several plant spacing tested one plant per hill is always bester than two plants per hill.